Combining Forecast Densities from VARs with Uncertain Instabilities - Anne Sofie Jore; James Mitchell; Shaun P. Vahey (Norges Bank, 2008)
Clark and McCracken (2008) argue that combining real-time point forecasts from VARs of output, prices and interest rates improves point forecast accuracy in the presence of uncertain model instabilities. In this paper, we generalize their approach to consider forecast density combinations and evaluations. Whereas Clark and McCracken (2008) show that the point forecast errors from particular equal-weight pairwise averages are typically comparable or better than benchmark univariate time series models, we show that neither approach produces accurate real-time forecast densities for recent US data. If greater weight is given to models that allow for the shifts in volatilities associated with the Great Moderation, predictive density accuracy improves substantially.
hdl:11250/2497786
Keywords: C32; C53; E37; 330; VAR models; density forecasts; uncertainty; combining forecasts; evaluating forecasts